Compensation Structure and Real CSR Reporting Activity: CEO Dollars and Sustainable Sense - Kohl, Elizabeth O.; Walsh , Steven T.; White, Reilly (Transformations In Business & Economics, 2026)
We utilize the voluntary Corporate Social Responsibility (CSR) environment in the Unted States (U.S.) to examine executive compensation and impact on real firm activities. Specifically, we consider both debt-like incentives of pension compensation and complex agency frictions arising from mixed executive compensation structures. We explore how the frictions between the short-term incentives of equity compensation and the long-term incentives of debt-type compensation influence real firm activities. Focusing on CEO pension compensation, we examine voluntary U.S. CSR reporting from 2006 to 2020. We find that firms offering higher pension compensation are less likely to initiate CSR reporting, but more likely to engage in ongoing voluntary CSR disclosure post-initiation. Additionally, ongoing CSR reporting is more prevalent when the CEO’s pension compensation is higher relative to other forms of compensation, such as cash-based (salary and bonus) and equity-based compensation (stock options). This indicates that CEOs with substantial pension compensation are incentivized to make decisions that preserve long-term firm value, ensuring their pensions are secured. Furthermore, we observe that CEOs are more likely to engage in ongoing CSR reporting in environments where the alignment of compensation structures with firm capital structures minimizes agency risk. This suggests that the alignment of incentive structures with real firm activities is more achievable in contexts where agency friction is minimized. These insights offer valuable implications for understanding agency theory, optimizing compensation incentives, and enhancing CSR reporting and voluntary disclosure practices.